A Centralized Processing Framework for Foliage Penetration Human Tracking in Multistatic Radar - Zhang, Jun; Jin, Tian; He, Yuan; Zhou, Zhimin (Společnost pro radioelektronické inženýrství, 2016)
A complete centralized processing framework is proposed for human tracking using multistatic radar in the foliage-penetration environment. The configuration of the multistatic radar system is described. Primary attention is devoted to time of arrival (TOA) estimation and target localization. An improved approach that takes the geometrical center as the TOA estimation of the human target is given. The minimum mean square error paring (MMSEP) approach is introduced for multi-target localization in the multistatic radar system. An improved MMSEP algorithm is proposed using the maximum velocity limitation and the global nearest neighbor criterion, efficiently decreasing the computational cost of MMSEP. The experimental results verify the effectiveness of the centralized processing framework.
Keywords: Multistatic radar; foliage penetration; human tracking; TOA estimation; target localization